International trade agreements and political economy - Riezman, Raymond Glenn (Tricontinental series on global economic issues ;, 2013)
This book presents a comprehensive view of recent developments in the theory of international trade agreements and political economy. This work introduces terms of trade effects and strategic behavior to the theory of international trade agreements. This is complemented by a careful analysis of how politics affects international trade agreements.